Geothermal energy resources in Ethiopia: Status review and insights from hydrochemistry of surface and groundwaters. (31st August 2021) - Burnside, Neil; Montcoudiol, Nelly; Becker, Kerry; Lewi, Elias
Abstract: Ethiopia has an estimated >10, 000 MW of geothermal energy potential, more than double its current power generating capacity (4, 400 MW). Electricity access stands at 44% of the total population, with 31% in rural areas, so effective development of this low‐carbon resource could make a significant impact to equitable delivery of electricity. However, geothermal energy exploitation must be done responsibly to protect valuable water resources under stress from climate‐change driven drought conditions and competing uses across agricultural, domestic, and industrial sectors. Our review provides progress updates on geothermal developments—which soon aim to deliver more than 1, 000 MW of electricity—and performs a high‐level assessment of hydrochemical data for ground and surface waters across Ethiopia. A water quality database was built using publicly available information and three quality control criteria: well‐defined sample location, cation‐anion balance (CAB) of ±10%, and clear fluid type definition. Ethiopia hosts two major geothermal water types, sodium‐alkalinity dominated in the Main Ethiopian Rift and sodium‐chloride dominated in the Afar Depression, separated by sodium‐mixed waters between Dofan‐Fantale and Meteka. H and O stable isotopes suggest a largely meteoric source for geothermal waters, with δ 18 O enrichment adding to evidence of a high enthalpy resource at Tendaho. Hydrochemical investigations provide critical information for successful delivery of sustainable geothermal energy developments. However, the current lack of data available for Ethiopia poses a significant challenge for completion of predevelopment baselines and ongoing environmental impact assessment. We encourage the release of unpublished findings from private companies and government agencies to build upon our database and demonstrate social and environmental responsibility in the development of Ethiopian geothermal resources. This article is categorized under: Engineering Water > Methods Abstract : The current exploration and development status of geothermal prospects in Ethiopia, complete with indicative water types for geothermal fluids.